Rancang Bangun SIMAB (Surat Izin Mengoperasikan Alat Berat) Untuk Keamanan dan Operasi Alat Berat Berbasis Arduino - Mangkona Mangkona; Abdul Halim; Muhammad Rezky Riannur; Hasan Basri; Merpatih Merpatih (Politeknik Negeri Samarinda, 2021)
Safety cannot be considered only important but is something that must be considered because negligence in Safety can result in serious injury to death. Therefore, SIMAB is an innovation to support security and safety, health, and the work environment for the convenience of working. SIMAB (License to Operate Electronic Heavy Equipment), this tool is capable of not providing operating access to those who do not have a license or password access, thereby increasing the security of the unit and workers. The research was conducted by the author with a literature review of related research, planning, designing, assembling, testing, measuring and reporting. This tool has met the author's expectations because it can work as expected. The case study that the author takes is the implementation of the 914G Caterpillar Wheel Loader unit. This tool is very satisfying and can create goals to improve security and safety in order to maintain work productivity, because it can work well.